The social transition and the technological mediation: the education from the oral societies to the information and knowledge society - María José HERNÁNDEZ SERRANO; Margarita GONZÁLEZ SÁNCHEZ (Ediciones Universidad de Salamanca, 2009)
Technologies witch had mediated in different moments had generated three historical stages. First, in the oral societies, the technology was the oral word; second, in the reader-writer cultures a cluster of graphic and phonological symbols; and in the current society will be Information and Communication Technologies (ICT). All these technologies will present new challenges for the educational environments; due to the educational systems had been charge of training individuals. Therefore, education will have to face up to new changes promoted by ITC in the current society.